Adaptive Judo and neuropathy: a mini review on motor skills, balance, and quality of life improvement - Nerozzi, Erika; Prada, Valeria; Pegreffi, Francesco; Grandis, Marina; Schenone, Angelo; Pierantozzi, Emanuela (Frontiers in Psychology, 2025)
IntroductionPeripheral neuropathies are progressive conditions characterized by muscle weakness, impaired balance, and reduced quality of life. Rehabilitation programs and adaptive sports have shown promise in mitigating these effects. This paper explores the potential of adaptive Judo to improve motor skills, balance, and overall quality of life in patients with neuropathy.MethodsWe review existing literature, analyze the benefits of Judo’s physical and cognitive demands, and propose adaptive guidelines for its implementation.ResultsThis study highlights Judo’s potential as a cost-effective and scalable intervention to support neuropathic patients.ConclusionThis review emphasizes the evidence-based benefits of adapted Judo training has the potential to transform both the physical and emotional health of neuropathic individuals.